Lowy, lowcy i zwierzyna w przyslowiach polskich - Dynak, Wladyslaw (Wroclaw : Tow. Przyjaciol Polonistyki Wroclawskiej, 1993)
Polish proverbs in which hunting, hunters and game are intrinsic themes.
Includes bibliographical references (p. 313-[327]) and index.
Keywords: Hunting -- Poland -- Quotations, maxims, etc; Proverbs, Polish -- History and criticism